Total Assets Turn Over, Debt to Assets Ratio, dan Debt to Equity Ratio terhadap Return on Assets pada Perusahaan Sub Sektor Asuransi - Mawarsih, Sri; Ramadhani, Fajri; Irawati, Limora; Fadillah, Nur (Universitas Islam Negeri Alauddin Makassar, 2020)
The expansion of insurance sub-sector companies in Indonesia is quite advanced, but on the other hand the profits of insurance sub-sector companies show instability during the observation period. This reseacrh aims to analyze the effect of Total Assets Turn Over, Debt to Assets Ratio and Debt to Equity Ratio on Return on Assets on Insurance sub sector companies listed on the Indonesian Stock Exchange (Bursa Efek Indonesia) Period 2014-2018. The research population was 16 companies, of which with the purposive sampling technique obtained 12 companies that met the criteria as a sample. Data analysis techniques used multiple linear regression analysis with the classical assumption test. The results Total Assets Turnover had a significant positive effect on Return on Assets, Debt to Assets Ratio had a significant negative effect on Return on Assets, and Debt to Equity Ratio did not significantly influence Return on Assets. Asset management is needed to properly regulate the level of loans on assets and capital of the company in order to reduce expenses and maximize the acquisition of Return on Assets.Keywords: Total Assets Turn Over, Debt to Assets Ratio, Debt to Equity Ratio, Return on AssetsPerkembangan perusahaan sub sektor asuransi di Indonesia cukup maju, namun disisi lain laba perusahaan sub sektor asuransi menunjukkan instabilitas selama periode pengamatan. Penelitian ini bertujuan menganalisis pengaruh Total Assets Turn Over, Debt to Assets Ratio dan Debt to Equity Ratio terhadap Return on Assets pada perusahaan sub sektor Asuransi yang terdaftar di BEI Periode 2014-2018. Populasi penelitian sebanyak 16 perusahaan, dari jumlah tersebut dengan teknik purposive sampling diperoleh 12 perusahaan yang memenuhi kriteria sebagai sampel. Teknik analisis data menggunakan Analisis regresi linier berganda dengan uji asumsi klasik. Hasil penelitian menunjukkan bahwa Total Assets Turnover berpengaruh positif signifikan terhadap Return on Assets, Debt to Assets Ratio berpengaruh negatif signifikan terhadap Return on Assets dan Debt to Equity Ratio tidak berpengaruh signifikan terhadap Return on Assets. Diperlukan pengelolaan aset dengan baik untuk mengatur tingkat pinjaman atas aset maupun modal perusahaan agar dapat mengurangi pengeluaran dan memaksimalkan perolehan Return on Assets.Kata Kunci: Total Assets Turn Over, Debt to Assets Ratio, Debt to Equity Ratio, Return on Assets